2018
DOI: 10.3991/ijet.v13i01.7811
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning at Engineering Universities: Benefits and Challenges

Abstract: Abstract-This paper concerns the cutting edge educational approaches incorporated into syllabuses of the most progressive Russian higher technical schools. The authors discuss one of the active methods in teaching foreign languages -collaborative learning implemented in e-courses. Theoretical and historical aspects of this approach are addressed, as are its suitability for engineering education and possible ways of introducing collaborative learning into ecourses. Collaborative learning technology offers wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 3 publications
1
35
0
11
Order By: Relevance
“…The in‐depth analysis of communication within each one was the primary form of analysis . By looking at the system's event log statistics, we know how students are learning, likes how often they raise questions, how many times they answer questions, how well they answer questions, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…The in‐depth analysis of communication within each one was the primary form of analysis . By looking at the system's event log statistics, we know how students are learning, likes how often they raise questions, how many times they answer questions, how well they answer questions, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, every individual student students learns his responsibility for peer group activity results [26]. Through has proven as effective way of learning in engineering discipline [27]. In contrast to this, Mark et.…”
Section: Literature Surveymentioning
confidence: 99%
“…Findings yielded by extant studies in this field revealed that the implementation of effective eLMS can promote academic achievement and interest in learning [10]. eLMS supports collaborative leaning methods, which refers to a collaborative activity of two or more learners who are working on achieving collective goals through the exchange of knowledge, learning, and reaching a consensus [11]. As a result, eLMS has an important impact on the higher education [12].…”
Section: Review Of Elmsmentioning
confidence: 99%